Migración y ecoturismo en la Reserva de la Biosfera de Los Tuxtlas (México) - Ángeles Piñar Álvarez; Martha Elena Nava Tablada; Diana Karina Viñas Oliva (PASOS Revista de Turismo y Patrimonio Cultural, 2011)
In 1988, in response to the deteriorating state of its natural resources, the Los Tuxtlas Biosphere Reserve (LTBR) is established in the Mexican state of Veracruz. Included within park boundaries are municipalities characterized by a high poverty rate and whose residents, due to restrictions placed on their traditional farming activities, have had to immigrate to the United States. At the same time, the biosphere reserve’s natural wealth has inspired environmentally friendly ecotourism initiatives. The purpose of our research was to analyze the relationship between migration and ecotourism in three communities located within park boundaries. We found that private and community-operated ecotourism businesses can provide inhabitants with adequate employment which in turn strengthens their ties to the community and reduces the need for them to emigrate away for financial reasons.